Ménétrier’s disease - Cheinquer, Hugo (2022)
The article discusses the case of a 32-year old, black woman, with a 10-year historyof chronic anemia and a cerebral abscess in 1996. She came to the EmergencyRoom at Hospital de Clínicas de Porto Alegre with a 15-day history of progressivedyspnea and pleural chest pain. She had signs of respiratory distress, diminishedvesicular breath sounds at both lung bases, and peripheral edema. Abdominalultrasonographic examination showed hepatomegaly and thickened gastric walls.Esophagogastroduodenoscopy showed an infiltrating lesion in the gastric fundus andbody, and a polypoid lesion in the gastric fundus. Endosonography showed an increasein gastric mucosal and submucosal thickness. On the 6th day after admission, thepatient had an episode of pulmonary thromboembolism. She was submitted toexploratory laparotomy. Abdominal lymph biopsy and liver biopsy were performed. Thepatient had an episode of venous thrombosis in the right superior limb. Subsequently,she presented anasarca and poor general state. On the 60th day, she presented dyspnea, and died as a result of cardiorespiratory arrest.